Child Exploitation by Parents in Early Marriage: Case Study in Cianjur West Java, Indonesia - Sopyan, Yayan; Muttaqin, Zezen Zainal; Solihat, Cucu; Aripin, Jaenal (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Parents should protect their children. Child exploitation by parents is a cruel act. One form of parental deprivation of children’s rights is to marry them at an early age. In Indonesia, the rate of early marriage is still above 10% of all marriages. There is a trend of early marriage with Arab men in tourist destinations such as Puncak-Cianjur, West Java, after the increasing number of tourist visits from the Middle East. This research used a qualitative research method with a phenomenological approach to explore informant' experiences, interpret their experiences, and give meaning to their experiences. Data were collected through observation and in-depth interviews using the Snow Bowling Effect method. The results of the research were analyzed using the framework method. This research found that parents determine the occurrence of early marriage. The drivers of early marriage are economic interests and religious dogma. Parents were influenced by biyong (marriage broker) in making decisions. Biyong took advantage of half of the dowry. Meanwhile, children’s consent to marry was influenced by religious doctrines that caused them to be altruistic and follow their parents' wishes. This research recommends the government be stricter in supervising foreign tourists and socializing the dangers of early marriage and mutáh marriage with foreigners.